Implementation for Improved Supervision and Control Industrial Business of Region Law Enforcement in DKI Jakarta - Miftakhirodhiyah, Lusy; Veithzal Rivai Zainal; Azis Hakim (Dinasti International Journal of Digital Business Management, 2023)
The rapid development of DKI Jakarta today can be seen from the many infrastructure developments in almost all areas of the capital city. Therapid development of development certainly affects the increase in industrial activities in DKI Jakarta. One of them is the increasing number of industrial business places in the DKI Jakarta area. This is what makes the government of DKI Jakarta Province flowto supervise and control industrial business premises. The phenomenon that occurs in the field is not only a positive impact produced by the business of industri, but the negative impact is no less important. Therefore, there needs to be intensive supervision so that this industrial business can be well organized. The purpose of this study is to see how the monitoring efforts carried out by the DKI Jakarta Provincial Government through the Civil Service Police Unit and faktor-what factors are obstacles in the implementation of the supervision. This research uses qualitative methods with data collection techniques including observation and interviews which are then processed and analyzed. The author uses descriptive analysis tools which are then presented in the form of explanatory descriptions with logical sentences so that they can be understood and understood.Based on the results of the study, the monitoring carried out by the DKI Jakarta Civil Service Police Unit in this case is the Section of Supervision and Control of Industrial Business Premises, namely through conservation, inspection and reporting of implementation well in terms of officers, but in terms of business actors, there are still business actors who alwaysavoid when there are officers who conduct direct inspections to the field. This is because there are obstacles that become obstacles in the implementation of supervision, including human resources, and business actors.